Young school children's use of digital devices and parental rules. Issue 4 (November 2015) - W. L. Goh, Wendy; Bay, Susanna; Chen, Vivian Hsueh-Hua
Highlights: Children voluntarily souk parental approval to use digital device. Major parental rule on device use is to set time limits. Playing games is the most common activity. Abstract: This paper looks at the usage of digital devices and parental rules among Singaporean children who are in their first two years of school. It examines the young children's usage of personal computers, mobile phones and tablet PCs. One hundred and sixteen children participated in the interviews. The children were asked about their access to the digital devices, whether they sought permission from parents as well as parental rules with regard to the usage. There is high home computer access of 96%. Children reported using personal computers mainly for playing games and for e-learning. All children interviewed reported having access to mobile phones. However, only 57% reported having access to tablet devices. Most of the children reported that they sought parental permission for use of these devices. There seems to be more parental rules for computer use than for mobile and tablet devices, the most common rules being not to play games until completion of homework, and health concerns such as having enough rest and not to strain the eyes. The children were also asked about their offline leisure activities, which are mostly spent on watching television and playing outdoor games. The paper also discusses gender differences and implications for parenting.